IMPLEMENTASI MEDIA VIDEO ANIMASI CERITA RAKYAT BERBASIS KEARIFAN LOKAL UNTUK MENINGKATKAN MOTIVASI DAN AKTIVITAS BELAJAR MUATAN PPKn SISWA KELAS II DI SD NEGERI 4 PANCASARI - Ni Nyoman Suantini; Dewa Bagus Sanjaya; I Nengah Suastika (Jurnal Media Komunikasi Pendidikan Pancasila dan Kewarganegaraan, 2022)
The aims of this study are (1) to find out and understand and provide an analysis of an increase in the learning motivation of second grade students at SD Negeri 4 Pancasari on the subject matter of Civics by implementing folklore animation video media based on local wisdom. (2) To find out and understand and provide an analysis of an increase in the learning activities of grade II students of SD Negeri 4 Pancasari on the content of Civics lessons by implementing folklore animation video media based on local wisdom. This research is a type of Classroom Action Research (CAR). The stages carried out in classroom action research (CAR) are (1) Planning, (2) Implementation, (3) Observation, (4) Reflection. The results of this study show (1) the average percentage of the learning motivation scale in the pre-action from 18.18% to 59.09% in the first cycle, and increased again in the second cycle to reach 90.90%. (2) the results of observations on the pre-action results of the average student learning activity are 15, 34%, in the first cycle the average result for student learning activities increased by 41.19%, and in the second cycle the average result for student learning activities increased, namely reached 88.92%. In this study, it can be concluded that the implementation of folklore animation video media can increase the motivation and learning activities of the second grade PPKN students at SD Negeri 4 Pancasari.